Correlation between impostor syndrome among doctoral students and supervisor empathy in Tunisia - Slimi, Oumayma; Muscella, Antonella; Marsigliante, Santo; Bahloul, Mourad (Frontiers in Psychology, 2024)
The prevalence of impostor syndrome among PhD students has increased rapidly in recent years, having very negative effects on their mental and psychological health as well as on their doctoral journey. This exploratory study aims to examine whether there is a causal correlation between impostor syndrome among PhD students and empathy among supervisors. This study encompasses 562 doctoral students (300 females, 262 males) and 152 Tunisian supervisors (68 females, 84 males). Employing ANOVA, significant influences on impostor syndrome emerge for gender, marital status, professional status, and the doctoral enrollment level (p < .001). Concurrently, supervisors' empathy is significantly affected by gender, marital status, and experience (p < .001). Linear regression establishes a noteworthy negative correlation (p = 0.045): a one-unit increase in empathy correlates with a 0.122-unit decrease in impostor syndrome. These findings underscore the intricate relationship between socio-professional factors, empathy, and impostor syndrome within the academic milieu, offering crucial insights for interventions and psychological support. The study aligns with the broader context of understanding mental health challenges in academia, emphasizing the imperative for ongoing support initiatives.